Coin-type lithium-ion secondary battery

JP7637228B2Active Publication Date: 2025-02-27NGK CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023510213
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-30
Filing Date
2021-11-18
Publication Date
2025-02-27
Estimated Expiration
2041-11-18

Smart Images

  • Figure 0007637228000002
    Figure 0007637228000002
  • Figure 0007637228000003
    Figure 0007637228000003
  • Figure 0007637228000004
    Figure 0007637228000004
Patent Text Reader

Abstract

Provided is a coin-type lithium ion secondary battery with which battery performance is less likely to deteriorate, even when being subjected to reflow soldering. This coin-type lithium ion secondary battery includes: a positive electrode layer; a negative electrode layer; a separator interposed between the positive electrode layer and the negative electrode layer; an electrolyte solution in which the positive electrode layer, the negative electrode layer, and the separator are immersed; and an exterior body that has a coin shape having a bulge on at least one face, and that is provided with a sealed space in which the positive electrode layer, the negative electrode layer, the separator, and the electrolyte solution are housed. This coin-type lithium ion secondary battery has: a main region in which all of the positive electrode layer, the negative electrode layer, and the separator overlap; and a peripheral region in which at least one of the positive electrode layer, the negative electrode layer, and the separator is not present. A battery swelling ratio, which is the ratio of a maximum value of the thickness of the coin-type lithium ion secondary battery in the main region to a minimum value of the thickness of the coin-type lithium ion secondary battery in the main region, is between 1.01 and 1.25.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coin-type lithium-ion secondary battery. [Background technology]

[0002] Coin-type lithium ion secondary batteries are widely used in various devices that require charging, and various coin-type lithium ion secondary batteries have been proposed. For example, Patent Document 1 (JP 2012-209178 A) discloses a coin-type battery in which a positive electrode is arranged on the inner surface of a positive electrode case that also serves as an external terminal, and a negative electrode is arranged on the inner surface of a negative electrode sealing plate that also serves as an external terminal, and the positive electrode and the negative electrode are opposed to each other via a separator. In such a coin-type battery, the periphery of the positive electrode case and the sealing plate are sealed via a gasket so as to hold an electrolyte inside. In the secondary battery as described above, a powder-dispersed positive electrode (so-called coated electrode) is used, which is prepared by applying and drying a positive electrode mixture containing a positive electrode active material, a conductive assistant, a binder, etc.

[0003] Generally, a powder-dispersed positive electrode contains a relatively large amount (for example, about 10% by weight) of components (binders and conductive additives) that do not contribute to capacity, resulting in a low packing density of the lithium composite oxide as the positive electrode active material. For this reason, there is a lot of room for improvement in terms of capacity and charge / discharge efficiency of the powder-dispersed positive electrode. Therefore, attempts have been made to improve the capacity and charge / discharge efficiency by forming the positive electrode or the positive electrode active material layer from a lithium composite oxide sintered plate. In this case, since the positive electrode or the positive electrode active material layer does not contain a binder or conductive additive, it is expected that a high capacity and good charge / discharge efficiency can be obtained by increasing the packing density of the lithium composite oxide. For example, Patent Document 2 (WO2019 / 221139) discloses a coin-type lithium-ion secondary battery having a positive electrode plate that is a lithium composite oxide sintered body plate, a negative electrode plate that is a titanium-containing sintered body plate, a separator, and an electrolyte inside an exterior body. It is said that by using the sintered body plate as an electrode, excellent heat resistance that enables reflow soldering can be obtained. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2012-209178 A [Patent Document 2] WO2019 / 221139 Summary of the Invention

[0005] In general, the main parts of the outer can (case and cap) that come into contact with the positive electrode (or positive electrode current collector) and the negative electrode (or negative electrode current collector) of a coin battery each have a flat shape that appears linear when viewed in cross section. However, when terminals are attached to these flat outer can parts and an attempt is made to mount the battery on a board by high-temperature reflow soldering, the flat outer can partly hits the electrode, damaging the electrode, which can easily degrade the battery performance.

[0006] The present inventors have now discovered that by giving a predetermined bulge to the shape of the outer can of a coin-type lithium-ion secondary battery, the battery performance is less likely to deteriorate even when subjected to reflow soldering.

[0007] SUMMARY OF THE PRESENT EMBODIMENTS An object of the present invention is to provide a coin-type lithium ion secondary battery whose battery performance is not easily deteriorated even when subjected to reflow soldering.

[0008] According to one aspect of the present invention, A positive electrode layer; A negative electrode layer; a separator interposed between the positive electrode layer and the negative electrode layer; an electrolyte solution impregnated in the positive electrode layer, the negative electrode layer, and the separator; an exterior body having a coin shape with a bulge on at least one surface and including a sealed space for accommodating the positive electrode layer, the negative electrode layer, the separator, and the electrolyte; A coin-type lithium-ion secondary battery comprising: the coin-type lithium-ion secondary battery has a main region where the positive electrode layer, the negative electrode layer, and the separator are all overlapped, and a peripheral region lacking at least one of the positive electrode layer, the negative electrode layer, and the separator; There is provided a coin-type lithium-ion secondary battery for reflow soldering, in which a battery bulge ratio, which is the ratio of the maximum thickness of the coin-type lithium-ion secondary battery in the main region to the minimum thickness of the coin-type lithium-ion secondary battery in the main region, is 1.01 to 1.25. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view of an example of a coin-type lithium ion secondary battery of the present invention. [Diagram 2] 1 is a SEM image showing an example of a cross section perpendicular to the plate surface of an oriented positive electrode plate. [Diagram 3] FIG. 3 is an EBSD image of a cross section of the oriented positive electrode plate shown in FIG. [Figure 4] FIG. 4 is a histogram showing the distribution of orientation angles of primary particles in the EBSD image of FIG. 3 on an area basis. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Coin-type lithium-ion secondary battery FIG. 1 shows a schematic diagram of an example of a coin-type lithium-ion secondary battery of the present invention. The lithium-ion secondary battery 10 shown in FIG. 1 includes a positive electrode layer 12, a negative electrode layer 16, a separator 20, an electrolyte 22, and an exterior body 24. The separator 20 is interposed between the positive electrode layer 12 and the negative electrode layer 16. The electrolyte 22 is impregnated into the positive electrode layer 12, the negative electrode layer 16, and the separator 20. The exterior body 24 includes an enclosed space, and the positive electrode layer 12, the negative electrode layer 16, the separator 20, and the electrolyte 22 are accommodated in the enclosed space. The exterior body 24 has a coin shape with a bulge on at least one surface. The coin-type lithium-ion secondary battery 10 includes a main region M where the positive electrode layer 12, the negative electrode layer 16, and the separator 20 are all overlapped, and a peripheral region lacking at least one of the positive electrode layer 12, the negative electrode layer 16, and the separator 20.P The battery bulge ratio, which is the ratio of the maximum thickness of the coin-type lithium-ion secondary battery 10 in the main region M to the minimum thickness of the coin-type lithium-ion secondary battery 10 in the main region M, is 1.01 to 1.25. By thus providing the outer can shape of the coin-type lithium-ion secondary battery 10 with a bulge of a predetermined ratio, the battery performance is less likely to deteriorate even when subjected to reflow soldering.

[0011] That is, when a terminal is attached to the flat outer can of a conventional battery and the battery is mounted on a board by high-temperature reflow soldering, the flat outer can comes into contact with the electrode, causing part of the electrode to break, which tends to deteriorate the battery performance, but this problem is conveniently solved by the present invention. This is thought to be because the shape of the outer can of the battery (particularly the main region M) is given a bulge of a certain ratio, which relieves the stress that can occur under high temperatures during reflow soldering (for example, the maximum temperature can reach 260°C), and as a result, damage to the electrodes is reduced.

[0012] Therefore, the lithium ion secondary battery 10 is preferably used for reflow soldering. For example, the lithium ion secondary battery 10 may further include a positive electrode terminal (not shown) joined to the outer surface of the exterior body 24 closer to the positive electrode layer 12, and a negative electrode terminal (not shown) joined to the outer surface of the exterior body 24 closer to the negative electrode layer 16. In this case, it is preferable that the positive electrode terminal and / or the negative electrode terminal is used for reflow soldering for mounting the coin-type lithium ion secondary battery 10 on a substrate. The positive electrode terminal is preferably joined to the positive electrode can 24a of the exterior body 24 by a method such as diffusion welding or laser welding. Similarly, the negative electrode terminal is preferably joined to the negative electrode can 24b of the exterior body 24 by a method such as diffusion welding or laser welding.

[0013] The exterior body 24 has a coin shape with a bulge on at least one surface. It is more preferable that the coin-shaped exterior body 24 has bulges on both surfaces. The battery bulge ratio, which is the ratio of the maximum thickness of the coin-type lithium-ion secondary battery 10 in the main region M to the minimum thickness of the coin-type lithium-ion secondary battery 10 in the main region M, is 1.01 to 1.25, preferably 1.02 to 1.23, more preferably 1.02 to 1.20, even more preferably 1.03 to 1.18, and particularly preferably 1.05 to 1.15. As described above, the main region M refers to a region where the positive electrode layer 12, the negative electrode layer 16, and the separator 20 all overlap. Therefore, the main region M is distinguished from the peripheral region P that lacks at least one (possibly all) of the positive electrode layer 12, the negative electrode layer 16, and the separator 20. The maximum and minimum thickness values ​​of the secondary battery 10 in the main region M can be measured using a commercially available laser displacement meter, and the battery swell ratio can be calculated using the measured maximum and minimum values. In this case, it is preferable to measure the thickness of the battery in the main region M for each of two straight lines perpendicular to the center of the lithium-ion secondary battery 10, calculate the battery swell ratio, and use the average value of the battery swell ratios obtained for the two straight lines.

[0014] The outer diameter of the lithium ion secondary battery 10 is not particularly limited, but is typically 8 to 25 mm, more typically 9.5 to 22 mm, and even more typically 12.5 to 20 mm.

[0015] The positive electrode layer 12 is a layer containing a positive electrode active material. The positive electrode layer 12 may be a powder dispersion type positive electrode (so-called coated electrode) prepared by applying and drying a positive electrode mixture containing a positive electrode active material (e.g., lithium cobalt oxide), a conductive assistant, a binder, etc., but is preferably a ceramic positive electrode plate, and more preferably a lithium composite oxide sintered body plate. The fact that the positive electrode layer 12 is a ceramic positive electrode plate or a sintered body plate means that the positive electrode layer 12 does not contain a binder or a conductive assistant. This is because even if the green sheet contains a binder, the binder disappears or is burned away during firing. And, since the positive electrode layer 12 does not contain a binder, there is an advantage that deterioration of the positive electrode due to the electrolyte 22 can be avoided. In addition, it is particularly preferable that the lithium composite oxide constituting the sintered body plate is lithium cobalt oxide (typically LiCoO2 (hereinafter sometimes abbreviated as LCO)). Various lithium composite oxide sintered plates or LCO sintered plates are known, and for example, the one disclosed in Patent Document 2 (WO2019 / 221139) can be used.

[0016] According to a preferred embodiment of the present invention, the lithium composite oxide sintered body plate constituting the positive electrode layer 12 is an oriented positive electrode plate containing a plurality of primary particles composed of a lithium composite oxide, and the plurality of primary particles are oriented with respect to the plate surface of the positive electrode plate at an average orientation angle of more than 0° and not more than 30°. FIG. 2 shows an example of a cross-sectional SEM image perpendicular to the plate surface of the oriented positive electrode plate, while FIG. 3 shows an electron backscatter diffraction (EBSD) image of the cross section perpendicular to the plate surface of the oriented positive electrode plate. FIG. 4 shows a histogram showing the distribution of the orientation angles of the primary particles 11 in the EBSD image of FIG. 3 on an area basis. In the EBSD image shown in FIG. 3, discontinuity of the crystal orientation can be observed. In FIG. 3, the orientation angle of each primary particle 11 is shown by a shade of color, and the darker the color, the smaller the orientation angle. The orientation angle is the inclination angle of the (003) plane of each primary particle 11 with respect to the plate surface direction. In FIGS. 2 and 3, the areas shown in black inside the oriented positive electrode plate are pores.

[0017] The positive electrode layer 12, which is an aligned positive electrode plate, is an aligned sintered body composed of a plurality of primary particles 11 bonded to each other. Each primary particle 11 is mainly plate-shaped, but may include those formed in a rectangular parallelepiped shape, a cubic shape, a spherical shape, etc. The cross-sectional shape of each primary particle 11 is not particularly limited, and may be rectangular, a polygon other than rectangular, circular, elliptical, or a complex shape other than these.

[0018] Each primary particle 11 is composed of a lithium composite oxide. The lithium composite oxide is Li x MO2 (where 0.05 < x < 1.10, M is at least one type of transition metal, and M typically includes one or more of Co, Ni, and Mn), which is an oxide represented by this formula. The lithium composite oxide has a layered rock salt structure. The layered rock salt structure refers to a crystal structure in which lithium layers and transition metal layers other than lithium are alternately stacked with an oxygen layer in between, that is, a crystal structure in which a transition metal ion layer and a single lithium layer are alternately stacked via oxide ions (typically an α-NaFeO2 type structure, that is, a structure in which transition metals and lithium are regularly arranged in the

[0111] axis direction of a cubic rock salt type structure). Examples of the lithium composite oxide include Li x CoO2 (lithium cobaltate), Li x NiO2 (lithium nickelate), Li x MnO2 (lithium manganate), Li x NiMnO2 (lithium nickel manganate), Li x NiCoO2 (lithium nickel cobaltate), Li x CoNiMnO2 (lithium cobalt nickel manganate), Li x CoMnO2 (lithium cobalt manganate), etc. are mentioned. Particularly preferably, it is Li x CoO2 (lithium cobaltate, typically LiCoO2). The lithium composite oxide may contain one or more elements selected from Mg, Al, Si, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, Ag, Sn, Sb, Te, Ba, Bi, and W.

[0019] As shown in Figures 3 and 4, the average value of the orientation angles of the primary particles 11, i.e., the average orientation angle, is greater than 0° and less than or equal to 30°. This brings about the following various advantages. First, since each primary particle 11 lies in a state inclined with respect to the thickness direction, the adhesion between each primary particle can be improved. As a result, the lithium ion conductivity between a certain primary particle 11 and other primary particles 11 adjacent to the primary particle 11 on both sides in the longitudinal direction can be improved, thereby improving the rate characteristics. Second, the rate characteristics can be further improved. This is 、 When lithium ions enter and leave the oriented positive electrode plate, the expansion and contraction in the thickness direction is more dominant than in the plate surface direction, so the expansion and contraction of the oriented positive electrode plate becomes smooth, and the entry and exit of lithium ions becomes smooth accordingly. In addition, when the positive electrode plate is oriented, it is expected that the stress applied to the electrode plate during reflow soldering is uniformed among the particles present in the electrode. Furthermore, this effect is more preferably exhibited in the case of the above-mentioned orientation.

[0020] The average orientation angle of the primary particles 11 is obtained by the following method. First, in an EBSD image of a rectangular region of 95 μm×125 μm observed at a magnification of 1000 times as shown in FIG. 3, three horizontal lines are drawn to divide the oriented positive electrode plate into four equal parts in the thickness direction, and three vertical lines are drawn to divide the oriented positive electrode plate into four equal parts in the plate surface direction. Next, the average orientation angle of the primary particles 11 is obtained by arithmetically averaging the orientation angles of all the primary particles 11 that intersect with at least one of the three horizontal lines and the three vertical lines. From the viewpoint of further improving the rate characteristics, the average orientation angle of the primary particles 11 is preferably 30° or less, more preferably 25° or less. From the viewpoint of further improving the rate characteristics, the average orientation angle of the primary particles 11 is preferably 2° or more, more preferably 5° or more.

[0021] As shown in FIG. 4, the orientation angle of each primary particle 11 may be widely distributed from 0° to 90°, but it is preferable that the majority of the orientation angles are distributed in the region of more than 0° and less than 30°. That is, when the cross section of the oriented sintered body constituting the oriented positive electrode plate is analyzed by EBSD, the total area of ​​the primary particles 11 (hereinafter referred to as low-angle primary particles) having an orientation angle of more than 0° and less than 30° with respect to the plate surface of the oriented positive electrode plate among the primary particles 11 contained in the analyzed cross section is preferably 70% or more, more preferably 80% or more, relative to the total area of ​​the primary particles 11 contained in the cross section (specifically, the 30 primary particles 11 used to calculate the average orientation angle). This makes it possible to increase the proportion of primary particles 11 with high mutual adhesion, thereby further improving the rate characteristics. In addition, it is more preferable that the total area of ​​the low-angle primary particles having an orientation angle of 20° or less is 50% or more relative to the total area of ​​the 30 primary particles 11 used to calculate the average orientation angle. Furthermore, the total area of ​​the low-angle primary particles having an orientation angle of 10° or less is more preferably 15% or more of the total area of ​​the 30 primary particles 11 used to calculate the average orientation angle.

[0022] Since each primary particle 11 is mainly plate-like, as shown in Figs. 2 and 3, the cross section of each primary particle 11 extends in a predetermined direction and is typically approximately rectangular. That is, when the cross section of the oriented sintered body is analyzed by EBSD, the total area of ​​the primary particles 11 having an aspect ratio of 4 or more among the primary particles 11 included in the analyzed cross section is preferably 70% or more, more preferably 80% or more, of the total area of ​​the primary particles 11 included in the cross section (specifically, the 30 primary particles 11 used to calculate the average orientation angle). Specifically, in the EBSD image shown in Fig. 3, this can further improve the mutual adhesion between the primary particles 11, and as a result, the rate characteristics can be further improved. The aspect ratio of the primary particles 11 is the value obtained by dividing the maximum Feret diameter of the primary particles 11 by the minimum Feret diameter. The maximum Feret diameter is the maximum distance between two parallel straight lines when the primary particle 11 is sandwiched between the two parallel straight lines on the EBSD image when the cross section is observed. The minimum Feret diameter is the minimum distance between two parallel lines when the primary particle 11 is sandwiched between the lines on an EBSD image.

[0023] The average particle size of the primary particles constituting the oriented sintered body is preferably 5 μm or more. Specifically, the average particle size of the 30 primary particles 11 used to calculate the average orientation angle is preferably 5 μm or more, more preferably 7 μm or more, and even more preferably 12 μm or more. This reduces the number of grain boundaries between the primary particles 11 in the direction in which lithium ions are conducted, improving the overall lithium ion conductivity, and thus improving the rate characteristics. The average particle size of the primary particles 11 is the arithmetic average of the circle-equivalent diameters of the primary particles 11. The circle-equivalent diameter is the diameter of a circle having the same area as each primary particle 11 on an EBSD image.

[0024] The lithium composite oxide sintered body plate constituting the positive electrode layer 12 preferably contains pores. When the sintered body contains pores, particularly open pores, the electrolyte can penetrate into the sintered body when the sintered body is incorporated into a battery as a positive electrode plate, and as a result, the lithium ion conductivity can be improved. This is because the conduction of lithium ions in the sintered body is by far faster than the conduction through the electrolyte in the pores, although there are two types of conduction: through the constituent particles of the sintered body and through the electrolyte in the pores.

[0025] The porosity of the lithium composite oxide sintered body plate constituting the positive electrode layer 12 is preferably 20 to 60%, more preferably 25 to 55%, further preferably 30 to 50%, and particularly preferably 30 to 45%. The pores are expected to provide a stress relief effect and a high capacity, and the mutual adhesion between the primary particles 11 can be improved, so that the rate characteristics can be further improved. The porosity of the sintered body is calculated by polishing the cross section of the positive electrode plate with a CP (cross section polisher) and then observing it with an SEM at a magnification of 1000, and binarizing the obtained SEM image. The average circle equivalent diameter of each pore formed inside the oriented sintered body is not particularly limited, but is preferably 8 μm or less. The smaller the average circle equivalent diameter of each pore, the more the mutual adhesion between the primary particles 11 can be improved, and as a result, the rate characteristics can be further improved. The average circle equivalent diameter of the pores is the arithmetic average of the circle equivalent diameters of 10 pores on the EBSD image. The circle equivalent diameter is the diameter of a circle having the same area as each pore on an EBSD image. Each pore formed inside the oriented sintered body is preferably an open pore that is connected to the outside of the lithium composite oxide sintered body plate.

[0026] The average pore size of the lithium composite oxide sintered body plate constituting the positive electrode layer 12 is preferably 0.1 to 10.0 μm, more preferably 0.2 to 5.0 μm, and further preferably 0.3 to 3.0 μm. Within the above range, local stress concentration in large pores is suppressed, and stress in the sintered body is easily released uniformly.

[0027] The thickness of the lithium composite oxide sintered body plate constituting the positive electrode layer 12 is preferably 60 to 600 μm, more preferably 70 to 550 μm, and further preferably 90 to 500 μm. Within such a range, the active material capacity per unit area is increased to improve the energy density of the lithium ion secondary battery 10, and deterioration of the battery characteristics (particularly an increase in the resistance value) due to repeated charging and discharging can be suppressed.

[0028] The negative electrode layer 16 is a layer containing a negative electrode active material. The negative electrode layer 16 may be a powder-dispersed type negative electrode (so-called coated electrode) prepared by applying and drying a negative electrode mixture containing a negative electrode active material, a conductive additive, a binder, etc., but is preferably a ceramic negative electrode plate, and more preferably a titanium-containing sintered body plate. The titanium-containing sintered body plate is preferably made of lithium titanate Li4Ti5O 12 It is preferable that the battery contains Li4Ti5O (hereinafter referred to as LTO) or niobium titanium composite oxide Nb2TiO7, and more preferably contains LTO. Although LTO is typically known to have a spinel structure, it can also adopt other structures during charging and discharging. For example, LTO is Li4Ti5O 12 (spinel structure) and Li7Ti5O 12 The reaction proceeds in the coexistence of two phases, i.e., spinel and tetrahydrofuran (rock salt structure). Therefore, LTO is not limited to a spinel structure.

[0029] The fact that the negative electrode layer 16 is a ceramic negative electrode plate or a sintered body plate means that the negative electrode layer 16 does not contain a binder or a conductive additive. This is because even if the green sheet contains a binder, the binder will disappear or be burned away during firing. Since the negative electrode plate does not contain a binder, the packing density of the negative electrode active material (e.g., LTO or Nb2TiO7) is high, and thus high capacity and good charge / discharge efficiency can be obtained. The LTO sintered body plate can be manufactured according to the method described in Patent Document 2 (WO2019 / 221139).

[0030] The titanium-containing sintered plate constituting the negative electrode layer 16 has a structure in which a plurality (i.e., a large number) of primary particles are bonded together. Therefore, it is preferable that these primary particles are composed of LTO or Nb2TiO7.

[0031] The thickness of the titanium-containing sintered body plate constituting the negative electrode layer 16 is preferably 70 to 500 μm, more preferably 85 to 400 μm, and more preferably 95 to 350 μm. The thicker the LTO sintered body plate, the easier it is to realize a battery with a high capacity and high energy density. The thickness of the titanium-containing sintered body plate can be obtained, for example, by measuring the distance between plate surfaces observed to be approximately parallel when the cross section of the titanium-containing sintered body plate is observed by SEM (scanning electron microscope).

[0032] The primary particle size, which is the average particle size of the multiple primary particles constituting the titanium-containing sintered plate, is preferably 1.2 μm or less, more preferably 0.02 to 1.2 μm, and further preferably 0.05 to 0.7 μm. Within such a range, it is easy to achieve both lithium ion conductivity and electronic conductivity, which contributes to improving the rate performance.

[0033] The titanium-containing sintered body plate constituting the negative electrode layer 16 preferably contains pores. By containing pores, particularly open pores, the sintered body plate can allow the electrolyte to penetrate into the sintered body plate when incorporated into a battery as a negative electrode plate, thereby improving the lithium ion conductivity. This is because the conduction of lithium ions in the sintered body is by far faster through the electrolyte in the pores than through the particles constituting the sintered body and through the electrolyte in the pores.

[0034] The porosity of the titanium-containing sintered plate constituting the negative electrode layer 16 is preferably 20 to 60%, more preferably 30 to 55%, and further preferably 35 to 50%. Within such a range, it is easy to achieve both lithium ion conductivity and electronic conductivity, which contributes to improving the rate performance.

[0035] The average pore size of the titanium-containing sintered plate constituting the negative electrode layer 16 is 0.08 to 5.0 μm, preferably 0.1 to 3.0 μm, and more preferably 0.12 to 1.5 μm. Within such a range, it is easy to achieve both lithium ion conductivity and electronic conductivity, which contributes to improving the rate performance.

[0036] The separator 20 is preferably a separator made of cellulose, polyolefin, polyimide, polyester (e.g., polyethylene terephthalate (PET)), or ceramic. A separator made of cellulose is advantageous in that it is inexpensive and has excellent heat resistance. Moreover, unlike widely used polyolefin separators that have poor heat resistance, a separator made of polyimide, polyester (e.g., polyethylene terephthalate (PET)), or cellulose not only has excellent heat resistance, but also has excellent wettability with respect to gamma-butyrolactone (GBL), which is an electrolyte component that has excellent heat resistance. Therefore, when an electrolyte containing GBL is used, the electrolyte can be sufficiently permeated into the separator (without being repelled). On the other hand, a separator made of ceramic has the advantage that it can be manufactured as a single integrated sintered body together with the positive electrode layer 12 and the negative electrode layer 16 as a whole, as well as being excellent in heat resistance. In the case of a ceramic separator, the ceramic constituting the separator is preferably at least one selected from MgO, Al2O3, ZrO2, SiC, Si3N4, AlN, and cordierite, and more preferably at least one selected from MgO, Al2O3, and ZrO2.

[0037] The electrolyte 22 is not particularly limited, and may be a commercially available electrolyte for lithium batteries, such as a solution in which a lithium salt is dissolved in a non-aqueous solvent such as an organic solvent. In particular, an electrolyte having excellent heat resistance is preferable, and such an electrolyte preferably contains lithium borofluoride (LiBF4) in a non-aqueous solvent. In this case, a preferred non-aqueous solvent is at least one selected from the group consisting of γ-butyrolactone (GBL), ethylene carbonate (EC), and propylene carbonate (PC), more preferably a mixed solvent of EC and GBL, a single solvent of PC, a mixed solvent of PC and GBL, or a single solvent of GBL, and particularly preferably a mixed solvent of EC and GBL or a single solvent of GBL. The non-aqueous solvent contains γ-butyrolactone (GBL), which increases the boiling point and significantly improves heat resistance. From this viewpoint, the volume ratio of EC:GBL in the non-aqueous solvent containing EC and / or GBL is preferably 0:1 to 1:1 (GBL ratio 50 to 100 volume%), more preferably 0:1 to 1:1.5 (GBL ratio 60 to 100 volume%), even more preferably 0:1 to 1:2 (GBL ratio 66.6 to 100 volume%), and particularly preferably 0:1 to 1:3 (GBL ratio 75 to 100 volume%). Lithium borofluoride (LiBF4) dissolved in the non-aqueous solvent is an electrolyte with a high decomposition temperature, which also brings about a significant improvement in heat resistance. The concentration of LiBF4 in the electrolytic solution 22 is preferably 0.5 to 2 mol / L, more preferably 0.6 to 1.9 mol / L, even more preferably 0.7 to 1.7 mol / L, and particularly preferably 0.8 to 1.5 mol / L.

[0038] The electrolyte solution 22 may further contain vinylene carbonate (VC) and / or fluoroethylene carbonate (FEC) and / or vinyl ethylene carbonate (VEC) and / or propane sultone (PS) as an additive. Both VC and FEC have excellent heat resistance. Therefore, by including such an additive in the electrolyte solution 22, an SEI film having excellent heat resistance can be formed on the surface of the negative electrode layer 16.

[0039] The exterior body 24 has a sealed space, and the positive electrode layer 12, the negative electrode layer 16, the separator 20, and the electrolyte 22 are accommodated in this sealed space. The exterior body 24 may adopt a structure generally adopted for coin batteries (see, for example, Patent Documents 1 and 2), and is not particularly limited. Typically, the exterior body 24 includes a positive electrode can 24a, a negative electrode can 24b, and a gasket 24c, and the positive electrode can 24a and the negative electrode can 24b are crimped via the gasket 24c to form a sealed space. The positive electrode can 24a and the negative electrode can 24b may be made of a metal such as stainless steel, and are not particularly limited. The gasket 24c may be a ring-shaped member made of an insulating resin such as polypropylene or polytetrafluoroethylene, and are not particularly limited. In addition, a gel-like solution may be applied to the gasket 24c to improve sealing properties. The type of solution used for the gel-like solution may be a heat-curing olefin-based solution, a synthetic rubber-based solution, or the like, but is not limited thereto as long as the solution has viscosity or adhesiveness after the solvent evaporates. Furthermore, the application method is not limited, and the gasket 24c may be dipped in the solution, or the solution may be applied to the gasket 24c using a dispenser or the like.

[0040] The lithium ion secondary battery 10 preferably further includes a positive electrode collector 14 and / or a negative electrode collector 18. The positive electrode collector 14 and the negative electrode collector 18 are not particularly limited, but are preferably metal foils such as copper foil or aluminum foil. The positive electrode collector 14 is preferably disposed between the positive electrode layer 12 and the positive electrode can 24a, and the negative electrode collector 18 is preferably disposed between the negative electrode layer 16 and the negative electrode can 24b. In addition, a positive electrode side carbon layer 13 is preferably provided between the positive electrode layer 12 and the positive electrode collector 14 from the viewpoint of reducing contact resistance. Similarly, a negative electrode side carbon layer 17 is preferably provided between the negative electrode layer 16 and the negative electrode collector 18 from the viewpoint of reducing contact resistance. Both the positive electrode side carbon layer 13 and the negative electrode side carbon layer 17 are preferably made of conductive carbon, and may be formed, for example, by applying a conductive carbon paste by screen printing or the like.

[0041] The battery element may be in the form of a unit cell of positive electrode layer 12 / separator 20 / negative electrode layer 16 as shown in Fig. 1, or in the form of a multi-layer cell having a plurality of unit cells. The multi-layer cell is not limited to a flat plate laminate structure in which flat plates or layers are stacked, but may have various laminate structures including the following examples. Note that any of the configurations exemplified below may be a single integrated sintered body as a whole cell laminate. - Folded structure: A laminated structure in which a sheet having a layered configuration including a unit cell and a current collecting layer is folded once or multiple times to form a multilayer (large area) structure. - Wound structure: A laminated structure in which sheets having a layered configuration including a unit cell and a current collecting layer are wound and integrated to form a multi-layered (large-area) laminated structure. - Multilayer ceramic capacitor (MLCC)-like structure: A laminated structure in which a stack unit of current collecting layer / positive electrode layer / ceramic separator layer / negative electrode layer / current collecting layer is repeated in the thickness direction to form a multi-layered (large-area) structure, with multiple positive electrode layers collecting current on one side (e.g. the left side) and multiple negative electrode layers collecting current on the other side (e.g. the right side).

[0042] In the bulging portion of the exterior body 24, a gap (internal space) may be formed between the exterior body 24 and the battery element. That is, the gap is between the exterior body 24 and the positive electrode layer 12 or the positive electrode current collector 14, and the gap is between the exterior body 24 and the negative electrode layer 16 or the negative electrode current collector 18. These gaps may be filled with the electrolyte solution 22, or an elastic member such as a spring, a washer, or a corrugated member may be inserted to absorb the expansion and contraction of the battery element accompanying charging and discharging. It is preferable that such an elastic member is made of a metal such as stainless steel in order to ensure electrical connection with the exterior body 24 (or the positive electrode terminal and the negative electrode terminal joined thereto).

[0043] Manufacturing method of the positive electrode plate The lithium composite oxide sintered body plate, which is a preferred embodiment of the positive electrode layer 12, may be produced by any method, but is preferably produced through (a) preparation of a lithium composite oxide-containing green sheet, (b) optional preparation of an excess lithium source-containing green sheet, and (c) lamination and firing of the green sheets.

[0044] (a) Preparation of lithium composite oxide-containing green sheet First, a raw powder composed of a lithium composite oxide is prepared. This powder preferably contains already synthesized plate-like particles (for example, LiCoO2 plate-like particles) having a composition of LiMO2 (M is as described above). The volumetric D50 particle size of the raw powder is preferably 0.3 to 30 μm. For example, the LiCoO2 plate-like particles can be produced as follows. First, LiCoO2 powder is synthesized by mixing Co3O4 raw powder and Li2CO3 raw powder and sintering (500 to 900 °C, 1 to 20 hours). The obtained LiCoO2 powder is pulverized in a pot mill to a volumetric D50 particle size of 0.2 μm to 10 μm to obtain plate-like LiCoO2 particles that can conduct lithium ions parallel to the plate surface. Such LiCoO2 particles can also be obtained by a method of crushing a green sheet using LiCoO2 powder slurry after grain growth, or a method of synthesizing plate-like crystals such as a flux method, hydrothermal synthesis, single crystal growth using a melt, or a sol-gel method. The obtained LiCoO2 particles are in a state where they can be easily cleaved along the cleavage plane. By cleaving the LiCoO2 particles by crushing, LiCoO2 plate-like particles can be produced.

[0045] The plate-like particles may be used alone as the raw material powder, or a mixture of the plate-like powder and other raw material powders (e.g., Co3O4 particles) may be used as the raw material powder. In the latter case, it is preferable to make the plate-like powder function as a template particle for providing orientation, and make the other raw material powders (e.g., Co3O4 particles) function as matrix particles that can grow along the template particle. In this case, it is preferable to use a powder in which the template particle and the matrix particle are mixed at 100:0 to 3:97 as the raw material powder. When the Co3O4 raw material powder is used as the matrix particle, the volume-based D50 particle size of the Co3O4 raw material powder is not particularly limited, and can be, for example, 0.1 to 1.0 μm, but is preferably smaller than the volume-based D50 particle size of the LiCoO2 template particle. The matrix particle can also be obtained by subjecting the Co(OH)2 raw material to heat treatment at 500°C to 800°C for 1 to 10 hours. In addition to Co3O4, Co(OH)2 particles or LiCoO2 particles may be used as the matrix particle.

[0046] When the raw powder is composed of 100% LiCoO2 template particles, or when LiCoO2 particles are used as matrix particles, a large (e.g., 90 mm x 90 mm square) and flat LiCoO2 sintered plate can be obtained by sintering. Although the mechanism is unclear, it is expected that volume change or local unevenness during sintering is unlikely to occur because LiCoO2 is not synthesized during the sintering process.

[0047] The raw material powder is mixed with a dispersion medium and various additives (binder, plasticizer, dispersant, etc.) to form a slurry. A lithium compound other than LiMO2 (for example, lithium carbonate) may be added to the slurry in an excess amount of about 0.5 to 30 mol% for the purpose of promoting grain growth or compensating for volatile matter during the firing process described later. It is preferable not to add a pore former to the slurry. The slurry is preferably stirred under reduced pressure to defoam it and adjusted to a viscosity of 4000 to 10000 cP. The obtained slurry is formed into a sheet to obtain a lithium composite oxide-containing green sheet. The green sheet thus obtained is an independent sheet-like molded body. An independent sheet (sometimes called a "self-supporting film") refers to a sheet that can be handled independently from other supports (including flakes with an aspect ratio of 5 or more). In other words, an independent sheet does not include a sheet that is fixed to another support (substrate, etc.) and integrated with the support (cannot be separated or is difficult to separate). The sheet forming is preferably performed using a forming method capable of applying a shear force to plate-like particles (e.g., template particles) in the raw material powder. In this way, the average inclination angle of the primary particles can be made to be more than 0° and 30° or less with respect to the plate surface. As a forming method capable of applying a shear force to the plate-like particles, the doctor blade method is suitable. The thickness of the lithium composite oxide-containing green sheet may be appropriately set so that it has the desired thickness as described above after firing.

[0048] (b) Preparation of green sheet containing excess lithium source (optional step) If desired, a green sheet containing an excess lithium source is prepared separately from the green sheet containing the lithium composite oxide. The excess lithium source is preferably a lithium compound other than LiMO2 in which components other than Li disappear by firing. A preferred example of such a lithium compound (excess lithium source) is lithium carbonate. The excess lithium source is preferably in powder form, and the volume-based D50 particle size of the excess lithium source powder is preferably 0.1 to 20 μm, more preferably 0.3 to 10 μm. The lithium source powder is then mixed with a dispersion medium and various additives (binder, plasticizer, dispersant, etc.) to form a slurry. The obtained slurry is preferably stirred under reduced pressure to defoam and the viscosity is preferably adjusted to 1000 to 20000 cP. The obtained slurry is formed into a sheet to obtain a green sheet containing an excess lithium source. The green sheet thus obtained is also an independent sheet-like molded body. The sheet forming can be performed by various well-known methods, but is preferably performed by a doctor blade method. The thickness of the excess lithium source-containing green sheet is preferably set so that the molar ratio (Li / Co ratio) of the Li content in the excess lithium source-containing green sheet to the Co content in the lithium composite oxide-containing green sheet is preferably 0.1 or more, more preferably 0.1 to 1.1.

[0049] (c) Stacking and firing of green sheets A green sheet containing a lithium composite oxide (e.g., a LiCoO2 green sheet) and, if desired, a green sheet containing an excess lithium source (e.g., a Li2CO3 green sheet) are placed on the lower setter in this order, and the upper setter is placed thereon. The upper setter and the lower setter are made of ceramics, preferably zirconia or magnesia. If the setter is made of magnesia, the pores tend to be small. The upper setter may have a porous structure or a honeycomb structure, or may have a dense structure. If the upper setter is dense, the pores tend to be small in the sintered plate, and the number of pores tends to be large. If necessary, the green sheet containing an excess lithium source is preferably cut to a size such that the molar ratio (Li / Co ratio) of the Li content in the green sheet containing an excess lithium source to the Co content in the green sheet containing a lithium composite oxide is preferably 0.1 or more, more preferably 0.1 to 1.1.

[0050] At the stage where the green sheet containing a lithium composite oxide (e.g., a LiCoO2 green sheet) is placed on the lower setter, this green sheet may be degreased as desired and then calcined at 600 to 850° C. for 1 to 10 hours. In this case, a green sheet containing an excess lithium source (e.g., a Li2CO3 green sheet) and an upper setter may be placed in this order on the calcined plate obtained.

[0051] The green sheet and / or calcined plate is sandwiched between setters, degreased as desired, and then heat-treated (fired) at a medium temperature range (e.g., 700 to 1000°C) to obtain a sintered lithium composite oxide plate. This firing step may be performed twice or once. When firing is performed twice, it is preferable that the first firing temperature is lower than the second firing temperature. The sintered plate thus obtained is also in the form of an independent sheet.

[0052] Manufacturing method of negative electrode plate The titanium-containing sintered plate, which is a preferred embodiment of the negative electrode layer 16, may be manufactured by any method. For example, an LTO sintered plate is preferably manufactured by (a) preparing an LTO-containing green sheet and (b) firing the LTO-containing green sheet.

[0053] (a) Preparation of LTO-containing green sheet First, lithium titanate Li4Ti5O 12A raw powder (LTO powder) consisting of the above is prepared. The raw powder may be a commercially available LTO powder or may be newly synthesized. For example, a powder obtained by hydrolyzing a mixture of titanium tetraisopropoxy alcohol and isopropoxy lithium may be used, or a mixture containing lithium carbonate, titania, etc. may be fired. The volumetric D50 particle size of the raw powder is preferably 0.05 to 5.0 μm, more preferably 0.1 to 2.0 μm. If the particle size of the raw powder is large, the pores tend to become large. In addition, if the raw particle size is large, a pulverization process (for example, pot mill pulverization, bead mill pulverization, jet mill pulverization, etc.) may be performed to obtain a desired particle size. Then, the raw powder is mixed with a dispersion medium and various additives (binder, plasticizer, dispersant, etc.) to form a slurry. A lithium compound other than LiMO2 (for example, lithium carbonate) may be added to the slurry in an excess of about 0.5 to 30 mol% for the purpose of promoting particle growth or compensating for volatiles during the firing process described later. It is preferable not to add a pore former to the slurry. The slurry is preferably stirred under reduced pressure to degas and adjust the viscosity to 4000 to 10000 cP. The obtained slurry is formed into a sheet to obtain an LTO-containing green sheet. The green sheet thus obtained is an independent sheet-like molded body. An independent sheet (sometimes called a "self-supporting film") refers to a sheet that can be handled independently from other supports (including flakes with an aspect ratio of 5 or more). In other words, an independent sheet does not include a sheet that is fixed to another support (substrate, etc.) and integrated with the support (cannot be separated or is difficult to separate). Sheet forming can be performed by various well-known methods, but is preferably performed by a doctor blade method. The thickness of the LTO-containing green sheet may be appropriately set so that it has the desired thickness as described above after firing.

[0054] (b) Firing of LTO-containing green sheet The LTO-containing green sheet is placed on a setter. The setter is made of ceramics, preferably zirconia or magnesia. The setter is preferably embossed. The green sheet thus placed on the setter is placed in a sheath. The sheath is also made of ceramics, preferably alumina. In this state, the sheet is degreased as desired and then fired to obtain an LTO sintered plate. This firing is preferably performed at 600 to 900°C for 1 to 50 hours, more preferably at 700 to 800°C for 3 to 20 hours. The sintered plate thus obtained is also in the form of an independent sheet. The temperature rise rate during firing is preferably 100 to 1000°C / h, more preferably 100 to 600°C / h. In particular, this temperature rise rate is preferably adopted in the temperature rise process from 300°C to 800°C, more preferably from 400°C to 800°C.

[0055] (c) Summary The LTO sintered plate can be preferably manufactured as described above. In this preferred manufacturing method, it is effective to 1) adjust the particle size distribution of the LTO powder and / or 2) change the heating rate during firing, which are considered to contribute to realizing various properties of the LTO sintered plate.

[0056] Coating method for integral sintered plate The integral sintered body plate having a three-layer structure of a positive electrode layer, a ceramic separator, and a negative electrode layer, which is preferably used in the lithium ion secondary battery of the present invention, is preferably entirely coated with a metal oxide layer. By entirely coating the integral sintered body plate with a metal oxide layer, it is possible to suppress delamination of the integral sintered body plate due to physical impact during battery assembly, and also to suppress capacity deterioration due to storage in a charged state. The coating of the integral sintered body plate with a metal oxide layer may be performed by any method, but it is preferable to, for example, i) prepare a coating liquid containing a metal compound, ii) immerse the integral sintered body plate in the coating liquid to allow the coating liquid to penetrate into the inside, iii) remove the integral sintered body and dry it, and then iv) heat-treat the integral sintered body to which the metal compound has been attached to convert the metal compound into a metal oxide, thereby forming a metal oxide layer. The coating liquid prepared in the above step i) is not particularly limited as long as it is a liquid containing a metal compound capable of forming a metal oxide layer by heat treatment in a solvent (preferably an organic solvent), but the metal compound is preferably at least one metal compound selected from the group consisting of Zr, Mg, Al, Nb, and Ti, and more preferably a metal alkoxide. Preferable examples of such metal compounds include metal alkoxides such as zirconium tetra-n-butoxide, magnesium diethoxide, triisopropoxyaluminum, niobium pentaethoxide, and titanium tetraisopropoxide. In the above step ii), the integral sintered body plate immersed in the coating liquid is preferably subjected to a vacuum or reduced pressure atmosphere, since the coating liquid can be sufficiently and efficiently penetrated into the interior of the integral sintered body plate. The drying in the above step iii) may be performed at room temperature, but may also be performed by heating. The heat treatment in the above step iv) is preferably performed at 300 to 700°C for 2 to 24 hours, more preferably at 350 to 550°C for 4 to 6 hours. In this way, an integral sintered body plate entirely covered with a metal oxide layer is obtained. EXAMPLES

[0057] The present invention will now be further illustrated by the following examples.

[0058] Example 1 A coin-type lithium ion secondary battery for reflow soldering was produced and evaluated as follows.

[0059] (1) Preparation of LCO green sheet (positive electrode green sheet) First, Co3O4 powder (manufactured by Coremax) and Li2CO3 powder (manufactured by Honjo Chemical Co., Ltd.) were mixed so that the molar ratio of Li / Co was 1.01, and then the mixture was kept at 780°C for 5 hours. The obtained powder was pulverized in a pot mill so that the volumetric D50 was 0.4 μm to obtain a powder consisting of LCO plate-like particles. 100 parts by weight of the obtained LCO powder, 100 parts by weight of a dispersion medium (toluene:isopropanol=1:1), 10 parts by weight of a binder (polyvinyl butyral: product number BM-2, manufactured by Sekisui Chemical Co., Ltd.), 4 parts by weight of a plasticizer (DOP: Di(2-ethylhexyl)phthalate, manufactured by Kurogane Kasei Co., Ltd.), 2 parts by weight of a dispersant (product name Rheodol SP-O30, manufactured by Kao Corporation), and 1 part by weight of ZrO2 (manufactured by Sigma-Aldrich Co., Ltd.) were mixed. The mixture was stirred under reduced pressure to degas and adjust the viscosity to 4000 cP to prepare an LCO slurry. The viscosity was measured using a Brookfield LVT viscometer. The slurry thus prepared was formed into a sheet on a PET film by a doctor blade method to form an LCO green sheet. The thickness of the LCO green sheet was adjusted to 100 μm after firing.

[0060] (2) Preparation of LTO green sheet (negative electrode green sheet) First, 100 parts by weight of LTO powder (volume standard D50 particle size 0.06 μm, manufactured by Sigma-Aldrich Japan LLC), 100 parts by weight of dispersion medium (toluene: isopropanol = 1:1), 20 parts by weight of binder (polyvinyl butyral: product number BM-2, manufactured by Sekisui Chemical Co., Ltd.), 4 parts by weight of plasticizer (DOP: Di (2-ethylhexyl) phthalate, manufactured by Kurogane Kasei Co., Ltd.), and 2 parts by weight of dispersant (product name Rheodol SP-O30, manufactured by Kao Corporation) were mixed. The obtained negative electrode raw material mixture was stirred and degassed under reduced pressure, and the viscosity was adjusted to 4000 cP to prepare an LTO slurry. The viscosity was measured with an LVT type viscometer manufactured by Brookfield. The slurry thus prepared was formed into a sheet shape on a PET film by the doctor blade method to form an LTO green sheet. The thickness of the LTO green sheet was set so that the thickness after firing was 100 μm.

[0061] (3) Preparation of MgO green sheet (separator green sheet) Magnesium carbonate powder (manufactured by Konoshima Chemical Co., Ltd.) was heat-treated at 900°C for 5 hours to obtain MgO powder. The obtained MgO powder and glass frit (manufactured by Nippon Frit Co., Ltd., CK0199) were mixed at a weight ratio of 4:1. 100 parts by weight of the obtained mixed powder (volume-based D50 particle size 0.4 μm), 100 parts by weight of a dispersion medium (toluene: isopropanol = 1:1), 20 parts by weight of a binder (polyvinyl butyral: product number BM-2, manufactured by Sekisui Chemical Co., Ltd.), 4 parts by weight of a plasticizer (DOP: Di (2-ethylhexyl) phthalate, manufactured by Kurogane Kasei Co., Ltd.), and 2 parts by weight of a dispersant (product name Rheodol SP-O30, manufactured by Kao Corporation) were mixed. The obtained raw material mixture was stirred under reduced pressure to defoam it, and the viscosity was adjusted to 4000 cP to prepare a slurry. The viscosity was measured with a Brookfield LVT type viscometer. The slurry thus prepared was formed into a sheet on a PET film by a doctor blade method to form a separator green sheet, the thickness of which was adjusted to 25 μm after firing.

[0062] (4) Lamination, compression and firing Three LCO green sheets (positive electrode green sheets), two MgO green sheets (separator green sheets) and two LTO green sheets (negative electrode green sheets) were stacked in this order, and the resulting laminate was subjected to CIP (cold isostatic pressing) at 200 kgf / cm 2 The green sheets were pressed together with a press. The laminate thus pressed was punched out into a disk shape with a diameter of 10 mm using a punching die. The obtained disk-shaped laminate was degreased at 600°C for 5 hours, and then heated to 800°C at 1000°C / h and held there for 10 minutes, followed by sintering, and then cooling. In this way, one integrated sintered plate (integrated electrode) was obtained, which included three layers: a positive electrode layer (LCO sintered layer) 12, a ceramic separator (MgO separator), and a negative electrode layer (LTO sintered layer).

[0063] (5) Metal oxide layer coating First, 10 g of 2-ethoxyethanol, 0.25 g of acetylacetone, and 1 g of zirconium tetra-n-butoxide were put into a container and stirred to prepare a coating solution. This solution was put into a container, and the integrated sintered body plate obtained in (4) above was immersed in it. The container was then put into a desiccator, evacuated to -95 kPa, and left for 3 minutes. After that, the inside of the desiccator was returned to the atmosphere, and the container containing the integrated sintered body plate was taken out. The integrated sintered body plate was taken out onto a nonwoven fabric wiper with tweezers, the coating solution was lightly wiped off, and the plate was dried at room temperature for 2 hours. The dried integrated sintered body plate was placed on an alumina setter and heat-treated at 400°C for 5 hours in a medium-sized super Kanthal furnace (manufactured by Kyowa Kounetsu Kogyo Co., Ltd.). In this way, an integrated sintered body plate (integrated electrode) entirely covered with a metal oxide layer (a layer composed of an oxide of Zr or a composite oxide of Zr and Li) was obtained.

[0064] (6) Preparation of lithium secondary batteries (6a) Bonding the negative electrode layer and negative electrode current collector with conductive carbon paste Acetylene black and polyimide amide were weighed out to a mass ratio of 3:1, and mixed with an appropriate amount of NMP (N-methyl-2-pyrrolidone) as a solvent to prepare a conductive carbon paste as a conductive adhesive. The conductive carbon paste was screen-printed on an aluminum foil as a negative electrode current collector. The integrated sintered body prepared in (5) above was placed so that the negative electrode layer 16 was contained within the undried print pattern (i.e., the area coated with the conductive carbon paste), and vacuum dried at 60°C for 30 minutes to prepare a structure in which the negative electrode layer and the negative electrode current collector were bonded via the negative electrode-side carbon layer. The thickness of the negative electrode-side carbon layer was set to 10 μm.

[0065] (6b) Preparation of positive electrode current collector with carbon layer Acetylene black and polyimide amide were weighed out to a mass ratio of 3:1 and mixed with an appropriate amount of NMP (N-methyl-2-pyrrolidone) as a solvent to prepare a conductive carbon paste. The conductive carbon paste was screen-printed on an aluminum foil as a positive electrode current collector, and then vacuum-dried at 60°C for 30 minutes to prepare a positive electrode current collector with a positive electrode carbon layer formed on the surface. The thickness of the positive electrode carbon layer was 5 μm.

[0066] (6c) Coin Cell Battery Assembly Between the positive and negative cans that would form the battery case, the positive electrode current collector, the positive electrode side carbon layer, the integrated sintered plate (LCO positive electrode layer, MgO separator and LTO negative electrode layer, the negative electrode side carbon layer, the negative electrode current collector, and the wave washer (manufactured by Misumi) were stacked in this order from the positive electrode can toward the negative electrode can, and after filling with electrolyte, the positive and negative cans were crimped together with a gasket to seal. In this way, a coin cell type lithium ion battery with a diameter of 12.5 mm and a thickness of 1.0 mm was produced. A lithium secondary battery was produced. The electrolyte used was a solution in which LiBF4 was dissolved in a PC organic solvent to a concentration of 1.5 mol / L. ThreeBond's 1171G was applied as a gasket sealant. The positive and negative cans were crimped using a crimping machine manufactured by Hosen Co., Ltd., with the thickness of the shim (hereinafter referred to as the knockout shim) attached to the knockout pin that presses the negative can being 0 mm, and the thickness of the shim on the positive can side being 50 μm.

[0067] (7) Battery evaluation The fabricated batteries were evaluated as follows.

[0068] <Battery outer diameter> The outer dimensions of the battery were measured using an image dimension measuring device (IM7000 manufactured by Keyence Corporation) to determine the outer diameter of the battery.

[0069] <Battery thickness and battery swelling ratio> A laser displacement meter (Keyence SI Series) was used to measure the thickness of the battery in the main area (i.e. the area where the three layers of the positive electrode layer, separator, and negative electrode layer overlap) for two straight lines perpendicular to the center of the battery. At this time, the minimum and maximum battery thickness in the main area for each straight line were measured. The average of the obtained maximum values ​​was taken as the battery thickness. In addition, the maximum battery thickness for each straight line was divided by the minimum battery thickness, and the average of the values ​​obtained for the two straight lines was taken as the battery swelling ratio.

[0070] <High temperature long term performance> The battery was mounted on the board by reflow soldering at a maximum temperature of 260°C. The mounted battery was charged at 2.7 V at 25°C with constant voltage (CV) and then discharged at 0.5 mA, and the discharge capacity at this time was recorded as the initial capacity. Next, in a 100°C environment, i) After constant voltage (CV) charging, ii) A total of 400 cycles of 20mA discharge for 1 second followed by a 2 second rest; A total of 100 cycles including the above (i.e., the above i) and ii) were counted as one cycle) were performed. After the 100 cycles, the battery was again charged at 2.7 V at 25° C. with constant voltage (CV), and then discharged at 0.5 mA, and the discharge capacity at this time was taken as the capacity after deterioration. The battery was deemed to have passed if the value obtained by dividing the capacity after deterioration by the initial capacity and multiplying the result by 100 was more than 95%, and was deemed to have failed if the value was not more than 95%.

[0071] Example 2 The batteries were fabricated and evaluated in the same manner as in Example 1, except that the thickness of the knockout shim that pressed the negative electrode can was 1 mm, and the thickness of the shim on the positive electrode can side was 50 μm, as the crimping conditions.

[0072] Example 3 The batteries were produced and evaluated in the same manner as in Example 1, except that the thickness of the knockout shim that pressed the negative electrode can was 2 mm, and the thickness of the shim on the positive electrode can side was 0 μm, as the crimping conditions.

[0073] Example 4 The batteries were produced and evaluated in the same manner as in Example 1, except that the thickness of the knockout shim that pressed the negative electrode can was 3 mm and the thickness of the shim on the positive electrode can side was 0 μm as the crimping conditions.

[0074] Example 5 A battery was produced and evaluated in the same manner as in Example 1, except for the following a) to c). a) In the lamination and compression bonding process, five LCO green sheets (positive electrode green sheets), four MgO green sheets (separator green sheets), and four LTO green sheets (negative electrode green sheets) were used, and the punching diameter of the laminate was set to 16.5 mm. b) The outer diameter of the battery can was 20 mm and the thickness was 1.6 mm. c) The crimping conditions were that the thickness of the knockout shim pressing against the negative electrode can was 2 mm, and the thickness of the shim on the positive electrode can side was 0 μm.

[0075] Example 6 (comparison) The batteries were produced and evaluated in the same manner as in Example 1, except that the thickness of the knockout shim that presses the negative electrode can was 0 mm and the thickness of the shim on the positive electrode can side was 100 μm as the crimping conditions.

[0076] Example 7 (comparison) The batteries were produced and evaluated in the same manner as in Example 1, except that the thickness of the knockout shim that pressed the negative electrode can was 4 mm and the thickness of the shim on the positive electrode can side was 0 μm as the crimping conditions.

[0077] result The evaluation results of the batteries produced in Examples 1 to 7 are shown in Table 1.

[0078] [Table 1]

Claims

1. A positive electrode layer; A negative electrode layer; a separator interposed between the positive electrode layer and the negative electrode layer; an electrolyte solution impregnated in the positive electrode layer, the negative electrode layer, and the separator; an exterior body having a coin shape with a bulge on at least one surface and including a sealed space for accommodating the positive electrode layer, the negative electrode layer, the separator, and the electrolyte; A coin-type lithium-ion secondary battery comprising: the coin-type lithium-ion secondary battery further includes a positive electrode terminal joined to an outer surface of the exterior body closer to the positive electrode layer, and a negative electrode terminal joined to an outer surface of the exterior body closer to the negative electrode layer, the coin-type lithium-ion secondary battery has a main region where the positive electrode layer, the negative electrode layer, and the separator are all overlapped, and a peripheral region lacking at least one of the positive electrode layer, the negative electrode layer, and the separator; A coin-type lithium-ion secondary battery for reflow soldering, having a battery swelling ratio, which is the ratio of the maximum thickness of the coin-type lithium-ion secondary battery in the main region to the minimum thickness of the coin-type lithium-ion secondary battery in the main region, of 1.01 to 1.

25.

2. 2. The coin-shaped lithium ion secondary battery for reflow soldering according to claim 1, wherein the coin-shaped exterior body has bulges on both sides.

3. 3. The coin-type lithium ion secondary battery for reflow soldering according to claim 1, wherein the lithium ion secondary battery has an outer diameter of 8 to 25 mm.

4. The coin-type lithium-ion secondary battery for reflow soldering according to any one of claims 1 to 3, wherein the exterior body comprises a positive electrode can, a negative electrode can, and a gasket, and the positive electrode can and the negative electrode can are crimped via the gasket to form the sealed space.

5. The coin-type lithium-ion secondary battery for reflow soldering according to any one of claims 1 to 4, wherein the positive electrode terminal and / or the negative electrode terminal is used for reflow soldering for mounting the coin-type lithium-ion secondary battery on a substrate.

6. The coin-type lithium ion secondary battery for reflow soldering according to any one of claims 1 to 5, wherein the positive electrode layer is a ceramic positive electrode plate.

7. 7. The coin-type lithium ion secondary battery for reflow soldering according to claim 6, wherein the ceramic positive electrode plate is a sintered lithium composite oxide plate.

8. 8. The coin-type lithium ion secondary battery for reflow soldering according to claim 7, wherein the lithium composite oxide is lithium cobalt oxide.

9. The coin-type lithium ion secondary battery for reflow soldering according to any one of claims 1 to 8, wherein the negative electrode layer is a ceramic negative electrode plate.

10. 10. The coin-type lithium ion secondary battery for reflow soldering according to claim 9, wherein the ceramic negative electrode plate is a titanium-containing sintered plate.

11. 11. The coin-type lithium ion secondary battery for reflow soldering according to claim 10, wherein the titanium-containing sintered plate contains lithium titanate or niobium titanium composite oxide.

12. The separator is made of cellulose, polyimide, polyester, MgO, Al 2 O 3 , ZrO 2 , SiC, Si 3 N 4 12. The coin-type lithium ion secondary battery for reflow soldering according to claim 1, which is made of a ceramic selected from the group consisting of AlN and cordierite.

13. The electrolyte solution is a solution of lithium borofluoride (LiBF) in a non-aqueous solvent consisting of at least one selected from the group consisting of γ-butyrolactone (GBL), ethylene carbonate (EC), and propylene carbonate (PC). 4 The coin-type lithium ion secondary battery for reflow soldering according to any one of claims 1 to 12, wherein the solution contains

Citation Information

Patent Citations

  • JP1981046536U

  • Coin-type lithium battery

    JP1995201323A

  • Flat battery and manufacturing method of the same

    JP2002175789A

  • Coin type battery

    JP2008084752A

  • Coin type electrochemical element

    JP2008123875A